Temporal location of events in language and (non) persistence of the past - Fabio Del Prete (Critical Hermeneutics, 2020)
The article reviews some analyses of temporal language in logical approaches to natural language semantics. It considers some asymmetries between past and future, manifested in language, which motivate the “standard view” of the non-reversibility of time and the persistence of the past. It concludes with a puzzle about the changing past which challenges the standard view.